2016
DOI: 10.1016/j.compositesb.2015.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Structural evaluation and design procedure for wood beams repaired and retrofitted with FRP laminates and honeycomb sandwich panels

Abstract: a b s t r a c tAs compared to other structural applications of polymeric composites, limited information is available on structural behavior of wood members strengthened with polymer composites. The focus of this paper is to evaluate the structural performance and practical use of wooden beams repaired and retrofitted with fiber-reinforced-polymeric (FRP) composites. The paper presents a summary results of an experimental study on the behavior of both Douglas Fir and Glulam wood beams repaired and retrofitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In addition to synthetic fiber reinforcement, natural fiber reinforcement may also be used, e.g., in the form of a nonwoven fabric. Experimental research has shown that correctly locating the reinforcement component has the potential to increase the bending characteristics of laminated wood in the case of application on the stressed tensile zone [21,29,30].…”
Section: Figurementioning
confidence: 99%
“…In addition to synthetic fiber reinforcement, natural fiber reinforcement may also be used, e.g., in the form of a nonwoven fabric. Experimental research has shown that correctly locating the reinforcement component has the potential to increase the bending characteristics of laminated wood in the case of application on the stressed tensile zone [21,29,30].…”
Section: Figurementioning
confidence: 99%
“…Figures (6) and ( 7) present details of the J-group and AJ-group specimens evaluated in this study, respectively. It should be noted that in this paper, the pultrusion direction is denoted as 0 0 directions, while direction contains θ degree clockwise with pultrusion direction is denoted as θ 0 direction and direction contains θ degree counter-clockwise with the pultrusion direction is denoted as -θ 0 direction.…”
Section: Specimens Preparationmentioning
confidence: 99%
“…In terms of high strength, light-weight, corrosion resistance and continuous manufacturing features, pultruded fiber reinforced polymer (PFRP) composites have been used in several successful applications both in newly constructed facilities applications [1][2][3] as well as repairing deteriorated structures [4][5][6]. For new structures, commercially produced, steel-like, unidirectional pultruded profiles are commonly used including H-girders [7][8][9], double-web beam girders [10][11], hybrid FRP-concrete girders [12], box girders [13], stay-in-place (SIP)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new technologies are being introduced to enhance wood based on hybrid composite designs [3][4][5][6][7]. Modern beams can thus be strengthened in the production phase [8], or old wooden beams can be repaired and retrofitted by adding FRP laminates [9][10][11][12][13][14][15][16][17] and honeycomb sandwich panels [18]. This strengthening can even be made reversible [19] or, in certain cases, adaptive [20].…”
Section: Introductionmentioning
confidence: 99%